Attention Deficit Disorder (ADDH) and Delinquency Subgroups - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Two subgroups of hyperactive children (25 non-delinquent and 9 delinquent) and 1 group of 34 non-delinquent normal children were evaluated from childhood to adolescence at the National Center for Hyperactive Children, Encino, CA, using auditory evoked response potential (AERP) measures and EEG recordings.